Fiber-Bragg-Grating Writing in Highly Nonlinear PM Fibers for Raman Fiber Lasers - Siekiera, Alexander; Engelbrecht, Rainer; Müller, E.; Schmauß, Bernhard (IEEE LEOS Winter Topicals Meeting Series, Innsbruck, Österreich, 12. - 14. Januar, 2009)
We describe the fabrication of flber-Bragg-gratings (FBG) in highly nonlinear polarization maintaining (PM) fibers with tight constraints concerning their spectral bandwidth and maximum reflectivity. The experimental setup for the inscription process and writing results are presented.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.fiberb